Parents’ concerns about the negative effects of television viewing on children’s behavior and school performance in Addis Ababa, Ethiopia - Yasin, Bethelhem; Desie, Yekoyealem (Bahir Dar Journal of Education, 2023)
Very little is known regarding parentsâ€™ concerns about the undesirable effects of unsupervised TV viewing on childrenâ€™s development in Ethiopia. This study investigated the extent and areas of parentsâ€™ concern about the harmful effects of TV viewing on childrenâ€™s behavior and school performance. A mixed-methods study design was employed. Quantitative data were collected from 390 parents of schoolchildren aged 7â€“15 in Addis Ababa using a standardized measure of parental concern. Qualitative data were also collected from Parent-Teacher-Student Association (PTSA) members using FGDs. Results showed a moderate-to-high level of parental concern about the adverse effects of viewing on childrenâ€™s behavior and school performance. The findings further indicated that childrenâ€™s learning of offensive language, premature exposure to sexual content, engagement in violent activities, and drug use were reported as parentsâ€™ areas of concern in relation to childrenâ€™s behavior. In the same way, disengagement in academic activities, mainly not doing homework, not studying, and getting poor exam results have been reported as parents’ areas of concern in relation to school performance. Statistically significant differences in level of concern across parentsâ€™ and childrenâ€™s socio-demographic characteristics were observed. As childrenâ€™s screen and digital media environment is fast-changing in Ethiopia, future studies in the area by child developmentalists, educationalists, and health professionals are highly warranted.